Understanding monetary policy and financial concepts - Central Bank of Nigeria, Monetary Policy Department; Monetary Policy Department, Central Bank of Nigeria (Abuja, Nigeria : Central Bank of Nigeria, 2016)
The book simplifies common concepts in monetary policy, economics, and related disciplines and specifically designed to equip and strengthen the knowledge of readers across all levels of finance and economics.
Includes index
oif 22/07/2021
Loans
Keywords: Monetary policy; Finance; Economics